CONCEPT OF MICROBIOLOGICAL GRAPH OF FEED AND FOOD PRODUCTION - B. Iegorov; А. Iegorova; К. Yeryganov (Zernovì Produkti ì Kombìkorma)
Compound feeds are favorable environments for microorganisms, namely bacteria and fungi. Both groups contain nonpathogenic, opportunistic and pathogenic members. Bacteria can cause infections, and fungi can cause mycotoxicoses, so controlling microbial contamination of feed is of great importance. Sources of microbial contamination of compound feed include both raw materials and the production environment: air, surfaces, equipment, and the hands and clothing of employees. As raw materials and pre-products move through production lines, they undergo certain processes that can either reduce or increase microbial contamination. The reducing processes include grain dehulling and high-temperature processing (moisture and heat treatment, conditioning, extrusion, expansion, drying of minerals, granulation), while the increasing processes include making preliminary mixtures, grinding, dosing and mixing, and the production of grits. In dosing and mixing, the contribution of each component is determined by its dose and has a two-way effect: the component contributes its microbiota, but its mass dilutes the mixture. The sequence of these processes represents a certain dynamics of microbial burden, which will result in the contamination level of the finished product lower or higher than in the initial raw material. This sequence can be represented as a microbiological graph, the vertices of which are the positive or negative contributions of the processes to the microbiological burden of the material. And the system of such vertices can be represented as a simple mathematical equation. Creating microbiological graphs for individual production lines or for the manufacture as a whole can help to understand the microbiological dynamics in a material or product and apply appropriate corrective measures to prevent microbiological hazards in the final product. This paper proposes a method of making a microbiological graph with two types of vertex designations for the IV generation compound feed production, as well as a mathematical apparatus for calculating the vertices of the graph.